Concepts of spawning targets - Environment Agency (Environment Agency North West, 2000)
This report discusses the concepts of spawning targets. Spawning target setting is based on the fact that the number of smolts produced by any given river is constrained by habitat availability. This means smolt numbers depend on spawner numbers up to a point, but thereafter smolt production reaches a ceiling. It has been shown, in some rivers at least, that the relationship between egg deposition and smolt production may approximately be described by a mathematical equation. The equation will vary between rivers and there is uncertainty over its exact form. The concept of Maximum Gain (MG) is explained and its application in fisheries management discussed. The author also critically examines the concept of Density Independent Mortality (DIM). Environment Agency Archives North West No date on publication. Date given is estimation. Environment Agency internal report, includes "Response to Dr Milner's targets"